Brain antioxidant regulation in mammals and anoxia-tolerant reptiles: balanced for neuroprotection and neuromodulation. - Rice, M; Forman, R; Chen, B; Avshalumov, M; Cragg, S; Drew, K (2002)
Reactive oxygen species (ROS) generated by mitochondrial respiration and other processes are often viewed as hazardous substances. Indeed, oxidative stress, defined as an imbalance between oxidant production and antioxidant protection, has been linked to several neurological disorders, including cerebral ischemia-reperfusion and Parkinson's disease. Consequently, cells and organisms have evolved specialized antioxidant defenses to balance ROS production and prevent oxidative damage. Research in our laboratory has shown that neuronal levels of ascorbate, a low molecular weight antioxidant, are ten-fold higher than those in much less metabolically active glial cells. Ascorbate levels are also selectively elevated in the CNS of anoxia-tolerant reptiles compared to mammals; moreover, plasma and CSF ascorbate concentrations increase markedly in cold-adapted turtles and in hibernating squirrels. Levels of the related antioxidant, glutathione, vary much less between neurons and glia or among species. An added dimension to the role of the antioxidant network comes from recent evidence that ROS can act as neuromodulators. One example is modulation of dopamine release by endogenous hydrogen peroxide, which we describe here for several mammalian species. Together, these data indicate adaptations that prevent oxidative stress and suggest a particularly important role for ascorbate. Moreover, they show that the antioxidant network must be balanced precisely to provide functional levels of ROS, as well as neuroprotection.